Economic growth and social welfare : operationalising normative social choice theory - Clarke, Matthew; Islam, Sardar M. N. (Boston : Elsevier, 2004)
This book studies the relationships between economic growth and social welfare and the policy implications of these relationships for development. These relationships are analysed in this book by operationalising normative social choice theory, with aggregate and hierarchical approaches developed and empirically applied.
Includes bibliographical references and index.
oif 01/09/15
Loan
Keywords: Economic development; Public welfare; Social choice